Desain Aplikasi Layanan Reservasi Bengkel Motor Online Pilihan Tepat untuk Servis Tanpa Repot - Nur Shidiq Ridwan, Azmi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study aims to design a mobile-based motorcycle workshop reservation application using the Design Thinking method to enhance user efficiency and convenience in accessing vehicle maintenance services. Data collection was conducted through a Google Forms survey of 32 respondents, providing insights into user needs, such as a reservation system, spare parts catalog, and digital payment methods. The results show that the reservation system is a primary need to reduce long queues, while the spare parts catalog feature offers convenience in accessing real-time product information. Digital payment methods were also identified as essential for more practical transactions. Through the Design Thinking approach, this application is expected to provide an innovative solution that meets user needs and increases satisfaction with motorcycle workshop services